Zigzag or spiral-shaped nanostructures improve mechanical stability in yttria-stabilized zirconia membranes for micro-energy conversion devices. (May 2019) - Shi, Yanuo; Fluri, Aline; Garbayo, Inigo; Schwiedrzik, J. Jakob; Michler, Johann; Pergolesi, Daniele; Lippert, Thomas; Rupp, Jennifer Lilia Marguerite
Abstract: Free-standing solid-state ion conducting thin film membranes are key components in micro-energy conversion devices such as micro-solid oxide fuel cells or electrolyzers. Through this work, we explore the design and fabrication of thin film architectures with either straight, zigzag or spiral-shaped columnar grain nanostructures of 8 mol% doped Yttria stabilized zirconia (8YSZ) in order to modify the ceramics elastic properties and mechanical stability for MEMS integration. We report that the zigzag and spiral-shaped nanomorphologies' can be engineered with a ∼44% reduced elastic modulus. Ultimately, this results in an increased fabrication yield when the thin ionic conductor thin film structures are turned into free-standing membranes as required for different micro energy converter applications. Raman spectroscopy reveals that the symmetry is lowered by the existence of monoclinic distortions in the cubic phase which modifies the elastic moduli of films with straight columnar structures. Fundamentally, we show here evidence that for yttria-stabilized zirconia modifications in membrane nano-architectures and strain can lead to phase changes, which agrees well with findings published in the 1970s based on applied external stress's on macroscopic structures (i.e. pellets). The influence of the change in nano-morphology on the cross-plane ionic conductivity is minor. The oxygen ion conducting thin film nanomorphology design exhibits potential to optimize grain connectivity and tortuosity by growth as either columnar, zigzag or spiral-shaped morphologies, in order to obtain membranes with controllable phases and elastic moduli for micro-energy conversion devices. Graphical abstract: The variation of nanomorphology influences the mechanical properties of oxygen ion conducting thin film applied in micro-energy conversion devices.Image 1 Highlights: Through this work, we explore the design and fabrication of thin film architectures with either straight, zigzag or spiral-shaped columnar grain nanostructures of 8 mol% doped Yttria stabilized zirconia (8YSZ). The zigzag and spiral-shaped nanomorphologies' can be engineered with a ∼44% reduced elastic modulus, resulting in an increased fabrication yield of 8YSZ free-standing membranes. Evidence is shown that for yttria-stabilized zirconia modifications in membrane nano-architectures and strain can lead to phase changes, well agreeing with findings from 1970s on applied external stress's on macroscopic structures. The oxygen ion conducting thin film nanomorphology design exhibits potential to optimize grain connectivity and tortuosity by growth as either columnar, zigzag or spiral-shaped morphologies.